The role of Special Assistant Teacher (SET) in differentiated learning for students with Dysgraphia in Indonesia language subjects: Analysis of scaffolding in the Zone of Proximal Development (ZPD) - Utami, Pramudya Ashya Novika; Rahmawati, Laili Etika; Sufanti, Main (BAHASTRA, 2026)
The urgency of this study is aligned with the fourth goal of the Sustainable Development Goals (SDG) and the fourth mission of Asta Cita Indonesia, which emphasize inclusive and equitable quality education. This study aims to: (1) describe the role of the special assistant teacher (SET) in differentiated learning for dysgraphic students in Indonesian language subjects; (2) explain the function of SET in implementing differentiated learning; and (3) analyze the collaboration between the Indonesian language teacher and SET in supporting dysgraphic students’ learning development. This qualitative study employed participatory observation in class 11 Social Studies at Al-Firdaus High School, Surakarta. Data were collected through classroom observation and interviews with the SET, the Indonesian language teacher, and dysgraphic students. Using scaffolding theory within the zone of proximal development (ZPD) as the analytical framework, the findings show that: (1) SET acts as a “more capable peer” by providing individual mentoring and simplifying instructions to enhance comprehension; (2) SET functions to maintain students’ focus, reduce task complexity, and provide guided examples tailored to students’ needs; and (3) effective collaboration includes joint planning, material and assessment adjustments, and coordinated assistance during learning. The study concludes that scaffolding within the ZPD supports dysgraphic students’ participation and that structured collaboration between SET and subject teachers strengthens inclusive differentiated learning practices.